Regional anesthesia in patients with pregnancy induced hypertension - Saravanan P Ankichetty; Ki Jinn Chin; Vincent W Chan; Raj Sahajanandan; Hungling Tan; Anju Grewal; Anahi Perlas (Wolters Kluwer Medknow Publications, 2013)
Pregnancy induced hypertension is a hypertensive disorder, which occurs in 5% to 7% of all pregnancies. These parturients present to the labour and delivery unit ranging from gestational hypertension to HELLP syndrome. It is essential to understand the various clinical conditions that may mimic preeclampsia and the urgency of cesarean delivery, which may improve perinatal outcome. The administration of general anesthesia (GA) increases morbidity and mortality in both mother and baby. The provision of regional anesthesia when possible maintains uteroplacental blood flow, avoids the complications with GA, improves maternal and neonatal outcome. The use of ultrasound may increase the success rate. This review emphasizes on the regional anesthetic considerations when such parturients present to the labor and delivery unit.